Understanding Cassini RPWS Antenna Signals Triggered by Dust Impacts. Issue 20 (22nd October 2019) - Ye, S.‐Y.; Vaverka, J.; Nouzak, L.; Sternovsky, Z.; Zaslavsky, A.; Pavlu, J.; Mann, I.; Hsu, H.‐W.; Averkamp, T. F.; Sulaiman, A. H.; Pisa, D.; Hospodarsky, G. B.; et al.
Abstract: Electric field antennas are capable of detecting dust impacts in different space environment. We analyze the dust impact signals detected by the Cassini Radio and Plasma Wave Science instrument at different locations around Saturn and compare them with dust impact signals simulated in laboratory conditions and numerically. The spacecraft potential, the size, and capacitance of the impacted element and ambient plasma have a strong effect on the amplitude and the shape of impact signals, providing important clues to understanding the signal generation mechanism. The voltage signal on the antenna is due to the separation of the impact generated charges, which occurs as electrons and ions can either escape (at different speeds) or be collected by the impacted element depending on the spacecraft potential. Key Points: Dust impact signals detected by Cassini can be understood as spacecraft potential perturbation due to the impact‐generated charges The shape of impact signal is consistent with the separate movements ofthe electrons and ions of the impact plasma Better‐controlled laboratory simulations of Cassini observations improved the understanding of impact signal generation